Sportwissenschaft - Steiner T; Raith S; Steegmann J; Fischer H; Hölzle F (Deutsche Zeitschrift für Sportmedizin)
Introduction: The incidence of bony injuries in the area of the facial skeleton is 23.9%. To minimize downtime in professional sports as muchas possible, protection masks are used today during training and matches. New non-contact scanning methods simplify their production and improve the application. As material resin-based carbon fiber laminates or polymethyl-methacrylate are generally utilized.Material & Methods: A positive, improved fit can be achieved bymethods of optical detection and the direct conversion by 3D printing. Using the example of a professional soccer player as a case study, we compared the conventional impression technique with the modern scanning method.Results: There was a considerably improved geometric correspondence between the mask produced by the digitally-assisted method and the skin surface of the patient, in comparison with the mask produced by conventional methods. The conventional mask showed a mean difference of 1.57mm with a maximum difference value of 5.62mm. The mask manufactured using the scanning method, however, showed an average deviation of only 0.99mm with a maximum difference value of 6.18mm.Conclusion: Our study reveals that the scan version is more precise in our case study than the conventionally-manufactured protection mask. Targeted support of the mask to protect the fracture istherebymore accurately adjustable by the clinician thereby.KEY WORDS: Protection Mask, Face Scan, 3D Printing, Soccer, Zygoma Fracture